INTRODUCTION OF THE INSTITUTIONALLY GUARANTEED JUDICIAL INDEPENDENCE INTO SERBIAN LAW - Gavrilović Grbović, Biljana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
The paper deals with the issue of introducing institutional guarantees of judicial independence into Serbian law. The institutional guarantee of judicial independence implies the permanence, immovability and material security of judges. There was awareness of the importance of the principle of judicial independence in Serbia even before the introduction of its institutional guarantees. The morality of judges was a guarantee of judicial independence until its legal security. However, given that the morality of judges got weaker, due to material scarcity, in the mid-19th century, the principle of judicial independence was first proclaimed as a constitutional category in the Regency Constitution; but without institutional guarantees. Therefore, young conservatives assess this move by the framers of the constitution as "empty idleness". Institutional guarantees were introduced only on the basis of the Law on Judges from 1881. However, although the fundamental need to legally secure the principle of judicial independence was emphasized, when the Law on Judges was adopted, it led to a discussion about instruments for institutionally securing this principle. Therefore, the paper focuses on the issue of what led to the divergence of views among Members of Parliament regarding the instruments for securing the core principle of the judiciary – the principle of judicial independence.